Assessment of HIV Screening Tests for Use in Preexposure Prophylaxis Programs. (27th June 2017) - Delaugerre, Constance; Antoni, Guillemette; Mahjoub, Nadia; Pialoux, Gilles; Cua, Eric; Pasquet, Armelle; Hall, Nolwenn; Tremblay, Cécile; Cotte, Laurent; Capitant, Catherine; Chaix, Marie-Laure; Meyer, Laurence; et al.
Summary: Preexposure prophylaxis programs involve frequent human immunodeficiency virus (HIV) testing. Antigen/antibody tests (rapid tests and immunoassays) should be preferred to avoid missing cases of acute HIV infection and to decrease the related risks of viral transmission and emergence of drug resistance. Abstract: Preexposure prophylaxis programs involve frequent human immunodeficiency virus (HIV) testing. We evaluated the sensitivity of 2 antigen/antibody immunoassays (Architect and Bioplex), 2 antibody-based rapid tests (Vikia-HIV-1/2 and Autotest-VIH), and 1 antigen/antibody rapid test (Alere HIV Combo) for the diagnosis of HIV infection. Among the 31 HIV-1–infected participants in the ANRS-IPERGAY trial, HIV-1 RNA was detected alone in only 2. The sensitivities of the Architect and Bioplex assays were 83% (95% confidence interval [CI], 76%–99%) and 82% (95% CI, 63%–94%), respectively. The sensitivities of the Vikia, Autotest, and Alere tests were 54% (95% CI, 34%–72%), 50% (95% CI, 31%–69%), and 78% (95% CI, 58%–91%), respectively. Antigen/antibody tests should be preferred to avoid missing cases of acute HIV infection and to decrease the related risks of viral transmission and emergence of drug resistance.